Habitat filtering and exclusion of weak competitors jointly explain fern species assemblage along a light and water gradient - Hui Zhang (Nature Portfolio, 2017)
Abstract Fern species are an important component of the diversity of forest plant communities, but very little is known about how fern communities assemble in different environments. In this study, we use multiple trait-based tests to examine the relationships between several key eco-physiological traits which are direct indicators of shade and drought tolerance, and the abundance of fern species in pine forest (PF), pine and mixed broad leaf forest (PMBF) and matured broad leaf forest (MBF) in southern China. These forests are characterized by decreasing light but increasing water availability during succession, and the fern communities correspondingly differ in species composition. We tested community assembly using functional trait distributions and found that habitat filtering and exclusion of weak competitive traits among coexisting species jointly explain fern shade tolerance as measured by photosynthetic capacity (PR), photosynthetic nutrient efficiency (PNUE and PPUE) and water use efficiency as measured by carbon isotope ratio (CIR), and constitute important determinants of fern community assembly in all three forests. These observed fern plant strategies are consistent with known responses of other plant taxa such as flowering plants in similar successional environments and illustrate the value of functional trait based analyses to study community assembly.